Dyspnea Among Patients With Chronic Total Occlusions Undergoing Percutaneous Coronary Intervention: Prevalence and Predictors of Improvement. Issue 12 (December 2017) - Qintar, Mohammed; Grantham, J. Aaron; Sapontis, James; Gosch, Kensey L.; Lombardi, William; Karmpaliotis, Dimitri; Moses, Jeffery; Salisbury, Adam C.; Cohen, David J.; Spertus, John A.; Arnold, Suzanne V.
Abstract : Background—: Dyspnea is a common angina equivalent that adversely affects quality of life, but its prevalence in patients with chronic total occlusions (CTOs) and predictors of its improvement after CTO percutaneous coronary intervention (PCI) are unknown. We examined the prevalence of dyspnea and predictors of its improvement among patients selected for CTO PCI. Methods and Results—: In the OPEN CTO registry (Outcomes, Patient health status, and Efficiency iN Chronic Total Occlusion) of 12 US experienced centers, 987 patients undergoing CTO PCI (procedure success 82%) were assessed for dyspnea with the Rose Dyspnea Scale at baseline and 1 month after CTO PCI. Rose Dyspnea Scale scores range from 0 to 4 with higher scores indicating more dyspnea with common activities. A total of 800 (81%) reported some dyspnea at baseline with a mean (±SD) Rose Dyspnea Scale of 2.8±1.2. Dyspnea improvement was defined as a ≥1 point decrease in Rose Dyspnea Scale from baseline to 1 month. Predictors of dyspnea improvement were examined with a modified Poisson regression model. Patients with dyspnea were more likely to be female, obese, smokers, and to have more comorbidities and angina. Among patients with baseline dyspnea, 70% reported less dyspnea at 1 month after CTO PCI. Successful CTO PCI was associated with more frequent dyspnea improvement than failure, even after adjustment for other clinical variables. Anemia, depression, and lung disease were associated with less dyspnea improvement after PCI. Conclusions—: Dyspnea is a common symptom among patients undergoing CTO PCI and improves significantly with successful PCI. Patients with other potentially noncardiac causes of dyspnea reported less dyspnea improvement after CTO PCI. Abstract : Supplemental Digital Content is available in the text.